(untitled) (Scientific Journal of Safety and Logistics, 2025)
The article examines the justification for the implementation of the National e-Invoicing System (KSeF) in Poland from the perspective of the financial security of the state. Contemporary tax systems are undergoing intensive digital transformation aimed at improving tax collection efficiency, reducing fiscal fraud, and increasing the transparency of economic transactions. One of the key tools in this process is electronic invoicing, which enables tax administrations to access transaction data in real time or near real time. The paper presents the structure and functioning of the KSeF system and analyses its potential impact on reducing the VAT gap and improving the stability of public revenues. A comparative analysis of e-invoicing systems implemented in other countries, particularly Italy, Brazil, Mexico, and India, is also conducted. The findings suggest that centralized e-invoicing systems may contribute to strengthening tax administration capabilities and limiting tax fraud. However, the implementation of such systems may also generate additional regulatory costs for businesses and require significant adjustments to corporate IT systems. The study concludes that the effectiveness of solutions such as KSeF depends not only on the level of digital fiscal control but also on the quality of public institutions, regulatory stability, and the level of social trust.